Pelatihan Kader Peduli Tablet Tambah Darah Bagi Remaja Putri Di SMP Dan SMA - Aida Fitriani; Hafsah Us; Fatiyani Fatiyani; Ika Friscila (Compromise Journal Community Proffesional Service Journal, 2024)
Adolescence is a period of human beings who are still experiencing excellent growth and development intellectually, physically and psychologically. The purpose of dedication is to improve the ability of young women to become Blood Add Tablet Care Cadres. The service method is carried out in junior and senior high schools in Syamtalira Bayu District for young women within a period of 3 months (June to August 2023). The implementation of community service is carried out by means of lectures, demonstrations, practicums, questions and answers and evaluations. The results obtained were 50 young women who were trained to become Blood Add Tablet Care Cadres at the junior and senior high school levels.